Pressure sensitive adhesive closing and sealing tapes for packaging. Specification for aluminium foil, paper, plasticized PVC, polyester, polyethylene, woven cloth and filament reinforced tapes Part 2, (29th November 1985) - British Standards Institution,
No abstract available